Using of the matrix representation of algorithms of the fast Fourier and Hartley transforms in the problems of “sliding” spectrum analysis - Zinchenko, Tatiana (My University, 2014)
Matrix formulae for calculating of the fast Fourier and Hartley transforms for a sequence of radar signal readings are obtained. The formulae obtained allow us to implement the “sliding” (or galloping”) spectrum analysis with rational using of information about the spectrum of a previous step for each new position of a time window. The matrix formulae of the Hartley transforms with an arbitrary base are obtained. These formulae are a generalization of the well-known Hartley formula for splitting of the initial sequence into the two sequences, namely, with the even and odd numbers.
Keywords: кафедра вищої математики імені проф. Можара В. І.; радіолокаційні сигнали; цифрова обробка; перетворення Фур'є; перетворення Хартлі; спектральний аналіз; радиолокационные сигналы; цифровая обработка; преобразование Фурье; преобразование Хартли; спектральный анализ; radar signals; digital processing; fast Fourier transform; fast Hartley transform; spectrum analysis